Developing A Multi-Linear Regression Model of Knowledge Management Factors Influencing Collaborative Projects in the Aviation Industry - Masrom, Asrul Nasid (International Journal of Sustainable Construction Engineering and Technology, 2023)
Effective knowledge management is emphasized as crucial in drafting strategic plans and initiating collaborative projects in the UAE aviation industry. The low awareness of knowledge management in the industry underscores the need to integrate it into collaborative projects for improved management operations and long-term growth in the global aviation market amid fierce competition and evolving technology trends. Hence, this study was carried out to formulate a multi linear regression model of knowledge management factors affecting the collaborative project for UAE aviation industry. A questionnaire survey was conducted among the respondents who associated with the aviation industry in UAE. A total of 373 sets of data was used to formulate the equation using SPSS software. It was found that the generated model has a strong correlation coefficient of 0.898 between the predictors and dependent variable. Also, strong coefficient of determination of 0,806 which indicates how well the selected independent variables collectively account for the variation in the dependent variables/predicators. This equation model can be applied to collaborative project in UAE aviation industry. This research contributes to the body of knowledge and to the aviation society.